Perbedaan Pendirian Sekolah Berdasarkan Jenis Kelas Islam Perspektif Hukum Islam - Helandri, Joni; Gazela, Rifki; Muzanni, Muzanni; Nasri, Halik; Harseto, Anggi (Hutanasyah : Jurnal Hukum Tata Negara, 2023)
This study aims to analyze the differences in the establishment of schools based on the type of Islamic class from the perspective of Islamic law. This study identifies the factors that influence the establishment of schools with Islamic classes, analyzes the differences in educational approaches between schools with Islamic classes and public schools, and explores the perspective of Islamic law regarding the establishment of schools with Islamic classes. The research method used is qualitative research with inductive data analysis. The research findings indicate that factors such as societal needs, approaches to religious education, and adherence to Islamic legal requirements influence the establishment of schools with Islamic classes. The results of the analysis also show differences in educational approaches between schools with Islamic classes and public schools, with an Islamic education approach that is more integrated in schools with Islamic classes. The perspective of Islamic law underscores the importance of fulfilling the requirements of Islamic law in the establishment of schools with Islamic classes, such as ensuring proper religious teaching, the presence of qualified teachers, and the management of funds according to Islamic principles. This research provides insights for educational policy makers and related parties in understanding the differences in the establishment of schools based on the type of Islamic class from the perspective of Islamic law.